Management of the Tahfidzul Qur'an Program in Shaping the Emotional Intelligence and Religious Character of Students - Oktaviani, Indah Ika; Hakim, Dian Mohammad; Hidayatullah, Muhammad Fahmi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The increasing moral challenges and emotional instability among students in the modern era have encouraged Islamic educational institutions to strengthen character development through religion-based educational programs. The Tahfidzul Qur'an program is considered a strategic medium for developing emotional intelligence and religious character through the internalization of Qur’anic values in students’ daily lives. This study aims to analyze the management of the Tahfidzul Qur'an program in shaping students’ emotional intelligence and religious character at Pondok Pesantren Tahfidzul Qur'an Nurul Furqon. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that: first, program planning was systematically designed based on the pesantren’s vision and mission by integrating the values of discipline, responsibility, and religious commitment; second, program implementation was carried out through structured mentoring, memorization submission, Kyai evaluation, and muroja’ah activities that fostered students’ cognitive, affective, and spiritual development; third, program supervision was conducted through intensive monitoring of memorization progress and worship practices, which strengthened the internalization of religious values and students’ emotional resilience. These findings indicate that effective management of the tahfidz program contributes significantly to the development of a Qur’anic personality balanced between spiritual maturity and emotional intelligence.